2015
DOI: 10.1021/jf5043954
|View full text |Cite
|
Sign up to set email alerts
|

Saponins, Especially Platyconic Acid A, from Platycodon grandiflorum Reduce Airway Inflammation in Ovalbumin-Induced Mice and PMA-Exposed A549 Cells

Abstract: We investigated the inhibitory effects of Platycodon grandiflorum root-derived saponins (Changkil saponins: CKS) on ovalbumin-induced airway inflammation in mice. CKS suppressed leukocytes number, IgE, Th1/Th2 cytokines, and MCP-1 chemokine secretion in bronchoalveolar lavage fluid. Also, ovalbumin-increased MUC5AC, MMP-2/9, and TIMP-1/-2 mRNA expression, NF-κB activation, leukocytes recruitment, and mucus secretion were inhibited by CKS treatment. Moreover, the active component of CKS, platyconic acid A (PA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Our previous study reported platyconic acid A (PA) isolation and purification (>95%) from Platycodi radix-derived saponin [19,27]. The chemical structure of PA is shown in Figure 1A.…”
Section: Preparation Of Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study reported platyconic acid A (PA) isolation and purification (>95%) from Platycodi radix-derived saponin [19,27]. The chemical structure of PA is shown in Figure 1A.…”
Section: Preparation Of Pamentioning
confidence: 99%
“…Recently, Platycodi radix, which contains various nutrients (amino acids, trace elements, and unsaturated fatty acids such as linoleic acid), has been considered to be a food source [15]. Our previous studies have reported that aqueous extract and saponin derived from Platycodi radix has protective effects on atopic dermatitis-like skin diseases, airway inflammation, osteoporosis, and metastasis [16][17][18][19][20][21][22]. Importantly, we reported that an aqueous extract from Platycodi radix and Platycodi radix-derived saponin inhibited various hepatic toxicant-induced liver diseases via numerous biological and pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…CKS extraction was prepared as demonstrated previously [Choi et al, ]. Platycodin D was purified from CKS and its purity was previously determined [Yoo et al, ; Choi et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous reported studies reveal that a water extract of the P. grandiflorum root ameliorates bronchial asthma, hyperlipidemia, hypercholesterolemia, and hepatic fibrosis [Choi et al, ]. P. grandiflorum root‐derived saponin extract (Changkil saponin; CKS) was recently shown to have anti‐oxidant [Lee et al, ], anti‐inflammatory [Choi et al, ], hepatoprotective [Khanal et al, ], and anti‐allergic [Han et al, ], and anti‐obesity [Hwang et al, ,] effects. CKS consist of triterpenoid saponins including deapio‐platycoside E, deapio‐platycodin D3, platycoside E, polygalacin D2, platyconic acid A, platycodin D3, platycodin D2, platycodin D, and 2′‐O‐acetylpolygalacin D2 [Noh et al, ].…”
mentioning
confidence: 99%
“…It belongs to the Campanulaceae family and is used as an herbal medicine and food in Asia (1). PR extracts have pharmacological potential for the treatment of inflammatory diseases (2,3). The consumption of PR in Korea was estimated to be greater than 4,000 tons/year and is constantly increasing mainly due to the tendency of consumers to consume healthy diets (4).…”
Section: Introduction 1)mentioning
confidence: 99%